Groundwater Quality Variations with Different Land Use Types in Belihul Oya Catchment - Herath, H.M.P.; Perera, M.P. (Department of Geography, University of Colombo, 2024)
Drainage basin characteristics, various land usage patterns with human interventions and seasonal differences in rainfall pattern, directly affect the water quality changes. Human interventions leading to land use changes may affect groundwater quality specially in agricultural areas. The objective of this study was examining the spatial variation of water quality changes in different types of land use in Belihuloya mini-catchment area. To investigate spatial variations of hydro-geochemical parameters, water samples were collected during North Eastern Monsoon (NEM) and 1st Inter Monsoon (1IM) season. Altogether, 20 water samples were selected containing 10 from springs, and 10 from the selected wells under recommended standards. The pH, and electrical conductivity (EC) were measured in the field using electrochemical methods. Titrimetric methods were used to determine the concentrations of chloride. HACH® digital titrator was used for all titrations. The anionic parameters Nitrate-N (NO3-–N), and sulphate (SO4-2), content were analysed using spectrophotometric methods. The cations, sodium (Na+), and calcium (Ca+2) were analysed using Atomic Absorption Spectrophotometric (AAS) methods (Perking Elmer- 2800). Finally, Inverse Distance weighting (IDW) method was used for contouring geochemical parameters in the study area using Arc GIS Ver.10.3. The study revealed that spatial variation of pH, and Ca in groundwater delineated several reasons behind water quality. However, spatial variation of NO3, SO4, Na, Cl, EC, and Ca, in groundwater have shown some variations parallel to land use categories. The well water showed a low pH levels than springs in the area. Spatial variation of Ca concentrations in water (Ca; 10.4-24 mg/l) in both spring and wells are higher along the down and middle catchment areas where predominantly Charnockitic is accumulated with limestone. According to the study, the groundwater quality variations have occurred due to variations of land use in the study area. Concentrations of most fertilizer driven parameters found in groundwater are higher along paddy lands, home gardens, tea and built-up areas, particularly in the middle catchment area where the earliest land use type was found as forests. The lower levels of above parameters in groundwater were observed along forests, scrubland, and grasslands. The use of high yielding varieties, chemical fertilization and the change in economic mode of production since 1956 have made considerable changes in the groundwater quality in the area.
Keywords: Groundwater; Water quality; land use; catchment areas